Erratum: “The Kepler Follow-up Observation Program. I. A Catalog of Companions to Kepler Stars from High-resolution Imaging” (2017, AJ, 153, 71) - Furlan, E.; Ciardi, D. R.; Everett, M. E.; Saylors, M.; Teske, J. K.; Horch, E. P.; Howell, S. B.; Belle, G. T. van; Hirsch, L. A.; Gautier, T. N.; Adams, E. R.; Barrado, D.; et al. (The Astronomical Journal, 2017)
We have added references to Tables 3 and 8 (last column in each table). Below is a sample of both tables; the full tables are available in machine-readable form.
Keywords: dept.phy

Coherent diffractive photoproduction of ρ0 mesons on gold nuclei at 200 GeV/nucleon-pair at the Relativistic Heavy Ion Collider - STAR Collaboration (Physical Review C, 2017)
The STAR Collaboration reports on the photoproduction of π+π- pairs in gold-gold collisions at a center-of-mass energy of 200 GeV/nucleon-pair. These pion pairs are produced when a nearly real photon emitted by one ion scatters from the other ion. We fit the π+π- invariant-mass spectrum with a combination of ρ0 and ω resonances and a direct π+π- continuum. This is the first observation of the ω in ultraperipheral collisions, and the first measurement of ρ-ω interference at energies where photoproduction is dominated by Pomeron exchange. The ω amplitude is consistent with the measured γp→ωp cross section, a classical Glauber calculation, and the ω→π+π- branching ratio. The ω phase angle is similar to that observed at much lower energies, showing that the ρ-ω phase difference does not depend significantly on photon energy. The ρ0 differential cross section dσ/dt exhibits a clear diffraction pattern, compatible with scattering from a gold nucleus, with two minima visible. The positions of the diffractive minima agree better with the predictions of a quantum Glauber calculation that does not include nuclear shadowing than with a calculation that does include shadowing. © 2017 American Physical Society.
28 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Elliptic flow of electrons from heavy-flavor hadron decays in Au + Au collisions at √sNN =200, 62.4, and 39 GeV - STAR Collaboration (Physical Review C, 2017)
We present measurements of elliptic flow (v2) of electrons from the decays of heavy-flavor hadrons (eHF) by the STAR experiment. For Au+Au collisions at sNN=200 GeV we report v2, for transverse momentum (pT) between 0.2 and 7 GeV/c, using three methods: the event plane method (v2{EP}), two-particle correlations (v2{2}), and four-particle correlations (v2{4}). For Au+Au collisions at sNN=62.4 and 39 GeV we report v2{2} for pT<2GeV/c. v2{2} and v2{4} are nonzero at low and intermediate pT at 200 GeV, and v2{2} is consistent with zero at low pT at other energies. The v2{2} at the two lower beam energies is systematically lower than at sNN=200 GeV for pT<1GeV/c. This difference may suggest that charm quarks interact less strongly with the surrounding nuclear matter at those two lower energies compared to sNN=200 GeV. © 2017 American Physical Society.
17 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Measurement of the cross section and longitudinal double-spin asymmetry for dijet production in polarized pp collisions at s =200 GeV - STAR Collaboration (Physical Review D, 2017)
We report the first measurement of the longitudinal double-spin asymmetry ALL for midrapidity dijet production in polarized pp collisions at a center-of-mass energy of s=200 GeV. The dijet cross section was measured and is shown to be consistent with next-to-leading order (NLO) perturbative QCD predictions. ALL results are presented for two distinct topologies, defined by the jet pseudorapidities, and are compared to predictions from several recent NLO global analyses. The measured asymmetries, the first such correlation measurements, support those analyses that find positive gluon polarization at the level of roughly 0.2 over the region of Bjorken-x>0.05. © 2017 American Physical Society.
21 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Measurements of jet quenching with semi-inclusive hadron+jet distributions in Au+Au collisions at sNN =200 GeV - STAR Collaboration (Physical Review C, 2017)
The STAR Collaboration reports the measurement of semi-inclusive distributions of charged-particle jets recoiling from a high transverse momentum hadron trigger, in central and peripheral Au+Au collisions at sNN=200 GeV. Charged jets are reconstructed with the anti-kT algorithm for jet radii R between 0.2 and 0.5 and with low infrared cutoff of track constituents (pT>0.2 GeV/c). A novel mixed-event technique is used to correct the large uncorrelated background present in heavy ion collisions. Corrected recoil jet distributions are reported at midrapidity, for charged-jet transverse momentum pT,jetch<30 GeV/c. Comparison is made to similar measurements for Pb+Pb collisions at s=2.76 TeV, to calculations for p+p collisions at s=200 GeV based on the pythia Monte Carlo generator and on a next-to-leading order perturbative QCD approach, and to theoretical calculations incorporating jet quenching. The recoil jet yield is suppressed in central relative to peripheral collisions, with the magnitude of the suppression corresponding to medium-induced charged energy transport out of the jet cone of 2.8±0.2(stat)±1.5(sys) GeV/c, for 10<pT,jetch<20 GeV/c and R=0.5. No medium-induced change in jet shape is observed for R<0.5. The azimuthal distribution of low-pT,jetch recoil jets may be enhanced at large azimuthal angles to the trigger axis, due to scattering off quasiparticles in the hot QCD medium. Measurement of this distribution gives a 90% statistical confidence upper limit to the yield enhancement at large deflection angles in central Au+Au collisions of 50±30(sys)% of the large-angle yield in p+p collisions predicted by pythia. © 2017 American Physical Society.
40 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Preface - Jain, F.; Broadbridge, C.; Tang, H. (International Journal of High Speed Electronics and Systems, 2017)
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy

Characterization and discrimination of basal cell carcinoma and normal human skin tissues using resonance Raman spectroscopy - Liu, C.-H.; Wu, B.; Boydston-White, S.; Beckman, H.; Sriramoju, V.; Sordillo, L.; Zhang, C.; Smith, J.; Zhang, L.; Shi, L.; Alfano, R.R. (Frontiers in Optics 2017, 2017)
Resonance Raman spectroscopy is used for rapid detection of skin BCC cancer. The cross-validated classification accuracy is achieved to be as high as 98% using nonnegative matrix factorization along with support vector machine statistical method. © OSA 2017.
2 citations (Crossref) [2023-10-31] Journal Abbreviation: Opt. InfoBase Conf. Pap
Keywords: Basal cell carcinoma; Classification accuracy; Factorization; Human skin; Matrix algebra; Nonnegative matrix factorization; Raman spectroscopy; Rapid detection; Resonance Raman spectroscopy; dept.phy

Charge-Dependent Directed Flow in Cu+Au Collisions at sNN =200 GeV - STAR Collaboration (Physical Review Letters, 2017)
We present the first measurement of charge-dependent directed flow in Cu+Au collisions at sNN=200 GeV. The results are presented as a function of the particle transverse momentum and pseudorapidity for different centralities. A finite difference between the directed flow of positive and negative charged particles is observed that qualitatively agrees with the expectations from the effects of the initial strong electric field between two colliding ions with different nuclear charges. The measured difference in directed flow is much smaller than that obtained from the parton-hadron-string-dynamics model, which suggests that most of the electric charges, i.e., quarks and antiquarks, have not yet been created during the lifetime of the strong electric field, which is of the order of, or less than, 1 fm/c. © 2017 American Physical Society.
17 citations (Crossref) [2023-10-31]
Keywords: Antiquarks; Charged particles; Colliding beam accelerators; Directed flow; Dynamics modeling; Electric fields; Nuclear charges; Pseudorapidities; Strong electric fields; Transverse momenta; dept.phy

Dijet imbalance measurements in Au+Au and pp collisions at sNN =200 GeV at STAR - STAR Collaboration (Physical Review Letters, 2017)
We report the first dijet transverse momentum asymmetry measurements from Au+Au and pp collisions at RHIC. The two highest-energy back-to-back jets reconstructed from fragments with transverse momenta above 2 GeV/c display a significantly higher momentum imbalance in heavy-ion collisions than in the pp reference. When reexamined with correlated soft particles included, we observe that these dijets then exhibit a unique new feature - momentum balance is restored to that observed in pp for a jet resolution parameter of R=0.4, while rebalancing is not attained with a smaller value of R=0.2. © 2017 American Physical Society.
18 citations (Crossref) [2023-10-31]
Keywords: Asymmetry measurements; Colliding beam accelerators; Germanium compounds; Gold compounds; Heavy ion collision; Heavy ions; Momentum; Momentum balances; Pp collisions; Rebalancing; Resolution parameters; Soft particles; Transverse momenta; dept.phy

A search for binary star companions to the KELT planet hosts and a comparison sample. i. results of DSSI observations - Coker, Carl T.; Gaudi, B. Scott; Pogge, Richard W.; Horch, Elliott (The Astronomical Journal, 2017)
We are conducting a search for binary companions around 11 hot-Jupiter hosts from the Kilodegree Extremely Little Telescope (KELT) survey and a large comparison sample of stars shown by KELT to not host a transiting hot Jupiter. The primary stars are bright (7.5 < V < 11) and of similar distance from Earth (100 < d < 300 pc). In this paper, we present the results of our observations using the Differential Speckle Survey Instrument. We observed 9 of the 14 KELT planet hosts that are visible from the northern hemisphere and 51 comparison stars, discovering two new potential companions and re-observing two previously known possible binary systems and one confirmed binary system. We provide an estimate of the chance alignment probability for our observed candidate binaries. © 2017 The American Astronomical Society. All rights reserved.
3 citations (Crossref) [2023-10-31]
Keywords: Astrometry; binaries: close; binaries: general; dept.phy; peer-reviewed; planets and satellites: detection; planets and satellites: formation

Validation of small Kepler transiting planet candidates in or near the habitable zone - Torres, Guillermo; Kane, Stephen R.; Rowe, Jason F.; Batalha, Natalie M.; Henze, Christopher E.; Ciardi, David R.; Barclay, Thomas; Borucki, William J.; Buchhave, Lars A.; Crepp, Justin R.; Everett, Mark E.; Horch, Elliott P.; et al. (The Astronomical Journal, 2017)
A main goal of NASA's Kepler Mission is to establish the frequency of potentially habitable Earth-size planets (). Relatively few such candidates identified by the mission can be confirmed to be rocky via dynamical measurement of their mass. Here we report an effort to validate 18 of them statistically using the BLENDER technique, by showing that the likelihood they are true planets is far greater than that of a false positive. Our analysis incorporates follow-up observations including high-resolution optical and near-infrared spectroscopy, high-resolution imaging, and information from the analysis of the flux centroids of the Kepler observations themselves. Although many of these candidates have been previously validated by others, the confidence levels reported typically ignore the possibility that the planet may transit a star different from the target along the same line of sight. If that were the case, a planet that appears small enough to be rocky may actually be considerably larger and therefore less interesting from the point of view of habitability. We take this into consideration here and are able to validate 15 of our candidates at a 99.73% (3σ) significance level or higher, and the other three at a slightly lower confidence. We characterize the GKM host stars using available ground-based observations and provide updated parameters for the planets, with sizes between 0.8 and 2.9 R ⊕. Seven of them (KOI-0438.02, 0463.01, 2418.01, 2626.01, 3282.01, 4036.01, and 5856.01) have a better than 50% chance of being smaller than 2 R ⊕ and being in the habitable zone of their host stars. © 2017. The American Astronomical Society. All rights reserved..
20 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/052-258-082-978-883, pop00029 tex.type: [object Object]
Keywords: dept.phy; methods: statistical; peer-reviewed; planetary systems; stars: individual (KOI-0172.02 = Kepler-69c ...); techniques: photometric

Characterizing K2 candidate planetary systems orbiting Low-mass stars. II. Planetary Systems observed during campaigns 1–7 - Dressing, Courtney D.; Vanderburg, Andrew; Schlieder, Joshua E.; Crossfield, Ian J. M.; Knutson, Heather A.; Newton, Elisabeth R.; Ciardi, David R.; Fulton, Benjamin J.; Gonzales, Erica J.; Howard, Andrew W.; Isaacson, Howard; Livingston, John; et al. (The Astronomical Journal, 2017)
We recently used near-infrared spectroscopy to improve the characterization of 76 low-mass stars around which K2 had detected 79 candidate transiting planets. 29 of these worlds were new discoveries that had not previously been published. We calculate the false positive probabilities that the transit-like signals are actually caused by non-planetary astrophysical phenomena and reject five new transit-like events and three previously reported events as false positives. We also statistically validate 17 planets (7 of which were previously unpublished), confirm the earlier validation of 22 planets, and announce 17 newly discovered planet candidates. Revising the properties of the associated planet candidates based on the updated host star characteristics and refitting the transit photometry, we find that our sample contains 21 planets or planet candidates with radii smaller than 1.25 R ⊕, 18 super-Earths (1.25-2 R ⊕), 21 small Neptunes (2-4 R ⊕), three large Neptunes (4-6 R ⊕), and eight giant planets (>6 R ⊕). Most of these planets are highly irradiated, but EPIC 206209135.04 (K2-72e, ), EPIC 211988320.01 (), and EPIC 212690867.01 () orbit within optimistic habitable zone boundaries set by the "recent Venus" inner limit and the "early Mars" outer limit. In total, our planet sample includes eight moderately irradiated 1.5-3 R ⊕ planet candidates (F p ≲ 20 F ⊕) orbiting brighter stars (Ks < 11) that are well-suited for atmospheric investigations with the Hubble, Spitzer, and/or James Webb Space Telescopes. Five validated planets orbit relatively bright stars (Kp < 12.5) and are expected to yield radial velocity semi-amplitudes of at least 2 m s-1. Accordingly, they are possible targets for radial velocity mass measurement with current facilities or the upcoming generation of red optical and near-infrared high-precision RV spectrographs. © 2017. The American Astronomical Society. All rights reserved..
68 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed; planetary systems; planets and satellites: fundamental parameters; stars: fundamental parameters; stars: late-type; stars: low-mass; techniques: spectroscopic

Investigating local parity violation in heavy-ion collisions using Λ helicity - Finch, L. E.; Murray, S. J. (Physical Review C, 2017)
We propose the measurement of net Λ and Λ helicity, correlated event by event with the magnitude and sign of charge separation along the event's magnetic field direction, as a probe to investigate the chiral magnetic effect (CME) in heavy-ion collisions. With a simple simulation model of heavy-ion events that includes effects of local parity violation, we estimate the experimental correlation signal that could be expected at RHIC given the results of previous measurements that are sensitive to the CME. © 2017 American Physical Society.
8 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Bulk properties of the medium produced in relativistic heavy-ion collisions from the beam energy scan program - STAR Collaboration (Physical Review C, 2017)
We present measurements of bulk properties of the matter produced in Au+Au collisions at √sNN=7.7,11.5,19.6,27, and 39 GeV using identified hadrons (π±, K±, p, and ¯p) from the STAR experiment in the Beam Energy Scan (BES) Program at the Relativistic Heavy Ion Collider (RHIC). Midrapidity (|y|<0.1) results for multiplicity densities dN/dy, average transverse momenta ⟨pT⟩, and particle ratios are presented. The chemical and kinetic freeze-out dynamics at these energies are discussed and presented as a function of collision centrality and energy. These results constitute the systematic measurements of bulk properties of matter formed in heavy-ion collisions over a broad range of energy (or baryon chemical potential) at RHIC.
332 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Exclusion of stellar companions to exoplanet host stars - Wittrock, Justin M.; Kane, Stephen R.; Horch, Elliott P.; Howell, Steve B.; Ciardi, David R.; Everett, Mark E. (The Astronomical Journal, 2017)
Given the frequency of stellar multiplicity in the solar neighborhood, it is important to study the impacts this can have on exoplanet properties and orbital dynamics. There have been numerous imaging survey projects established to detect possible low-mass stellar companions to exoplanet host stars. Here, we provide the results from a systematic speckle imaging survey of known exoplanet host stars. In total, 71 stars were observed at 692 and 880 nm bands using the Differential Speckle Survey Instrument at the Gemini-north Observatory. Our results show that all but two of the stars included in this sample have no evidence of stellar companions with luminosities down to the detection and projected separation limits of our instrumentation. The mass-luminosity relationship is used to estimate the maximum mass a stellar companion can have without being detected. These results are used to discuss the potential for further radial velocity follow-up and interpretation of companion signals. © 2017. The American Astronomical Society. All rights reserved..
9 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/064-303-042-496-092, pop00140 tex.type: [object Object]
Keywords: dept.phy; peer-reviewed; planetary systems; techniques: high angular resolution

Energy dependence of J/ψ production in Au + Au collisions at √sNN=39,62.4 and 200GeV - STAR Collaboration (Physics Letters B, 2017)
The inclusive J/ψ transverse momentum spectra and nuclear modification factors are reported at mid-rapidity (|y|<1.0) in Au + Au collisions at sNN = 39, 62.4 and 200 GeV taken by the STAR experiment. A suppression of J/ψ production, with respect to the production in p+p scaled by the number of binary nucleon–nucleon collisions, is observed in central Au + Au collisions at these three energies. No significant energy dependence of nuclear modification factors is found within uncertainties. The measured nuclear modification factors can be described by model calculations that take into account both suppression of direct J/ψ production due to the color screening effect and J/ψ regeneration from recombination of uncorrelated charm–anticharm quark pairs. © 2017 The Author
28 citations (Crossref) [2023-10-31] Citation Key Alias: pop00010 tex.ids: [object Object] tex.type: [object Object]
Keywords: dept.phy; peer-reviewed

Direct virtual photon production in Au+Au collisions at √sNN=200 GeV - STAR Collaboration (Physics Letters B, 2017)
We report the direct virtual photon invariant yields in the transverse momentum ranges 1<pT<3 GeV/c and 5<pT<10 GeV/c at mid-rapidity derived from the dielectron invariant mass continuum region 0.10<Mee<0.28 GeV/c2 for 0–80% minimum-bias Au+Au collisions at sNN=200 GeV. A clear excess in the invariant yield compared to the nuclear overlap function TAA scaled p+p reference is observed in the pT range 1<pT<3 GeV/c. For pT>6 GeV/c the production follows TAA scaling. Model calculations with contributions from thermal radiation and initial hard parton scattering are consistent within uncertainties with the direct virtual photon invariant yield. © 2017 The Author
34 citations (Crossref) [2023-10-31] Citation Key Alias: pop00009 tex.ids: [object Object] tex.type: [object Object]
Keywords: dept.phy; peer-reviewed

Determination of critical cooling rates in metallic glass forming alloy libraries through laser spike annealing. - Bordeenithikasem, Punnathat; Liu, Jingbei; Kube, Sebastian A; Li, Yanglin; Ma, Tianxing; Scanley, B Ellen; Broadbridge, Christine C; Vlassak, Joost J; Singer, Jonathan P; Schroers, Jan (Scientific reports, 2017)
The glass forming ability (GFA) of metallic glasses (MGs) is quantified by the critical cooling rate (R C). Despite its key role in MG research, experimental challenges have limited measured R C to a minute fraction of known glass formers. We present a combinatorial approach to directly measure R C for large compositional ranges. This is realized through the use of compositionally-graded alloy libraries, which were photo-thermally heated by scanning laser spike annealing of an absorbing layer, then melted and cooled at various rates. Coupled with X-ray diffraction mapping, GFA is determined from direct R C measurements. We exemplify this technique for the Au-Cu-Si system, where we identify Au56Cu27Si17 as the alloy with the highest GFA. In general, this method enables measurements of R C over large compositional areas, which is powerful for materials discovery and, when correlating with chemistry and other properties, for a deeper understanding of MG formation.
44 citations (Crossref) [2023-10-31] Place: England Bordeenithikasem, Punnathat. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut, 06511, USA. Liu, Jingbei. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut, 06511, USA. Kube, Sebastian A. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut, 06511, USA. Li, Yanglin. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut, 06511, USA. Ma, Tianxing. Department of Mechanical and Aerospace Engineering, Rutgers University, Piscataway, New Jersey, 08854, USA. Scanley, B Ellen. Department of Physics, Southern Connecticut State University, New Haven, Connecticut, 06515, USA. Broadbridge, Christine C. Department of Physics, Southern Connecticut State University, New Haven, Connecticut, 06515, USA. Vlassak, Joost J. School of Engineering and Applied Science, Harvard University, Cambridge, Massachusetts, 02138, USA. Singer, Jonathan P. Department of Mechanical and Aerospace Engineering, Rutgers University, Piscataway, New Jersey, 08854, USA. Schroers, Jan. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut, 06511, USA. jan.schroers@yale.edu. Erratum in (EIN)
Keywords: dept.phy; peer-reviewed

Global Λ hyperon polarization in nuclear collisions - STAR Collaboration (Nature, 2017)
The extreme energy densities generated by ultra-relativistic collisions between heavy atomic nuclei produce a state of matter that behaves surprisingly like a fluid, with exceptionally high temperature and low viscosity. Non-central collisions have angular momenta of the order of 1,000h, and the resulting fluid may have a strong vortical structure that must be understood to describe the fluid properly. The vortical structure is also of particular interest because the restoration of fundamental symmetries of quantum chromodynamics is expected to produce novel physical effects in the presence of strong vorticity. However, no experimental indications of fluid vorticity in heavy ion collisions have yet been found. Since vorticity represents a local rotational structure of the fluid, spin-orbit coupling can lead to preferential orientation of particle spins along the direction of rotation. Here we present measurements of an alignment between the global angular momentum of a non-central collision and the spin of emitted particles (in this case the collision occurs between gold nuclei and produces Λ baryons), revealing that the fluid produced in heavy ion collisions is the most vortical system so far observed. (At high energies, this fluid is a quark-gluon plasma.) We find that Λ and hyperons show a positive polarization of the order of a few per cent, consistent with some hydrodynamic predictions. (A hyperon is a particle composed of three quarks, at least one of which is a strange quark; the remainder are up and down quarks, found in protons and neutrons.) A previous measurement that reported a null result, that is, zero polarization, at higher collision energies is seen to be consistent with the trend of our observations, though with larger statistical uncertainties. These data provide experimental access to the vortical structure of the nearly ideal liquid created in a heavy ion collision and should prove valuable in the development of hydrodynamic models that quantitatively connect observations to the theory of the strong force. © 2017 Macmillan Publishers Limited, part of Springer Nature. All rights reserved.
512 citations (Crossref) [2023-10-31] Finch
Keywords: Article; baryon; dept.phy; gluon; heavy ion; hydrodynamics; hyperon; polarization; priority journal; proton; quantum mechanics; quark; viscosity

Measurement of d0 azimuthal anisotropy at midrapidity in Au+Au collisions at √sNN =200 GeV - STAR Collaboration (Physical Review Letters, 2017)
We report the first measurement of the elliptic anisotropy (v2) of the charm meson D0 at midrapidity (|y|<1) in Au+Au collisions at sNN=200 GeV. The measurement was conducted by the STAR experiment at RHIC utilizing a new high-resolution silicon tracker. The measured D0 v2 in 0%-80% centrality Au+Au collisions can be described by a viscous hydrodynamic calculation for a transverse momentum (pT) of less than 4 GeV/c. The D0 v2 as a function of transverse kinetic energy (mT-m0, where mT=pT2+m02) is consistent with that of light mesons in 10%-40% centrality Au+Au collisions. These results suggest that charm quarks have achieved local thermal equilibrium with the medium created in such collisions. Several theoretical models, with the temperature-dependent, dimensionless charm spatial diffusion coefficient (2πTDs) in the range of ∼2-12, are able to simultaneously reproduce our D0 v2 result and our previously published results for the D0 nuclear modification factor. © 2017 American Physical Society.
80 citations (Crossref) [2023-10-31] Citation Key Alias: pop00003 tex.ids: [object Object] tex.type: [object Object]
Keywords: Anisotropy; Au+Au collisions; Azimuthal anisotropy; Bosons; Colliding beam accelerators; Hadrons; Hydrodynamic calculation; Kinetic energy; Kinetics; Local thermal equilibrium; Nuclear modification factors; STAR experiment; Star trackers; Temperature dependent; Transverse momenta; dept.phy

Young stars in the periphery of the Large Magellanic Cloud - Moni Bidin, C.; Casetti-Dinescu, D. I.; Girard, T. M.; Zhang, L.; Méndez, R. A.; Vieira, K.; Korchagin, V. I.; van Altena, W. F. (Monthly Notices of the Royal Astronomical Society, 2017)
Despite their close proximity, the complex interplay between the two Magellanic Clouds, the Milky Way and the resulting tidal features, is still poorly understood. Recent studies have shown that the Large Magellanic Cloud (LMC) has a very extended disc strikingly perturbed in its outskirts.We search for recent star formation in the far outskirts of the LMC, out to ~30° from its centre.We have collected intermediate-resolution spectra of 31 young star candidates in the periphery of the LMC and measured their radial velocity, stellar parameters, distance and age. Our measurements confirm membership to the LMC of six targets, for which the radial velocity and distance values match well with those of the Cloud. These objects are all young (10-50 Myr), main-sequence stars, projected between 7° and 13° from the centre of the parent galaxy. We compare the velocities of our stars with those of a disc model, and find that our stars have low to moderate velocity differences with the disc model predictions, indicating that they were formed in situ. Our study demonstrates that recent star formation occurred in the far periphery of the LMC, where thus far only old objects were known. The spatial configuration of these newly formed stars appears ring-like with a radius of 12 kpc and a displacement of 2.6 kpc from the LMC's centre. This structure, if real, would be suggestive of a star formation episode triggered by an off-centre collision between the Small Magellanic Cloud and the LMC's disc. © 2016 The Authors.
13 citations (Crossref) [2023-10-31]
Keywords: Magellanic Clouds; Stars: early-type; dept.phy; peer-reviewed

Observations of binary stars with the Differential Speckle Survey Instrument. VII. Measures from 2010 September to 2012 February at the WIYN Telescope - Horch, Elliott P.; Casetti-Dinescu, Dana I.; Camarata, Matthew A.; Bidarian, Akbar; Altena, William F. van; Sherry, William H.; Everett, Mark E.; Howell, Steve B.; Ciardi, David R.; Henry, Todd J.; Nusdeo, Daniel A.; Winters, Jennifer G. (The Astronomical Journal, 2017)
We report on speckle observations of binary stars carried out at the WIYN Telescope over the period from 2010 September through 2012 February, providing relative astrometry for 2521 observations of 883 objects, 856 of which are double stars and 27 of which are triples. The separations measured span a range of 0.01-1.75 arcsec. Wavelengths of 562, 692, and 880 nm were used, and differential photometry at one or more of these wavelengths is presented in most cases. 66 components were resolved for the first time. We also estimate detection limits at 0.2 and 1.0 arcsec for high-quality observations in cases where no companion was seen, a total of 176 additional objects. Detection limits vary based on observing conditions and signal-to-noise ratio, but are approximately 4 mag at 0.2 arcsec and 6 mag at 1.0 arcsec on average. Analyzing the measurement precision of the data set, we find that the individual separations obtained have linear measurement uncertainties of approximately 2 mas, and photometry is uncertain to approximately 0.1 mag in general. This work provides fundamental, well-calibrated data for future orbit and mass determinations, and we present three first orbits and total mass estimates of nearby K-dwarf systems as examples of this potential. © 2017. The American Astronomical Society. All rights reserved..
55 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/110-417-913-195-546, pop00017 tex.type: [object Object]
Keywords: binaries: visual; dept.phy; peer-reviewed; techniques: high angular resolution; techniques: interferometric; techniques: photometric

HAT-P-67b: An extremely low density Saturn transiting an F-subgiant confirmed via doppler tomography - Zhou, G.; Bakos, G. Á.; Hartman, J. D.; Latham, D. W.; Torres, G.; Bhatti, W.; Penev, K.; Buchhave, L.; Kovács, G.; Bieryla, A.; Quinn, S.; Isaacson, H.; et al. (The Astronomical Journal, 2017)
We report the discovery of HAT-P-67b, which is a hot-Saturn transiting a rapidly rotating F-subgiant. HAT-P-67b has a radius of Rp=2.085 -0.071 +0.096 RJ, and orbites a M∗ = 1.642-0.072 +0.155 M, R∗ = 2.546-0.099 +0.0084 R host star in a ∼4.81 day period orbit. We place an upper limit on the mass of the planet via radial velocity measurements to be Mp < 0.59 MJ, and a lower limit of >0.056 MJ by limitations on Roche lobe overflow. Despite being a subgiant, the host star still exhibits relatively rapid rotation, with a projected rotational velocity of v sin I∗ = 35.8 ±1.1 km s-1, which makes it difficult to precisely determine the mass of the planet using radial velocities. We validated HAT-P-67b via two Doppler tomographic detections of the planetary transit, which eliminate potential eclipsing binary blend scenarios. The Doppler tomographic observations also confirm that HAT-P-67b has an orbit that is aligned to within 12, in projection, with the spin of its host star. HAT-P-67b receives strong UV irradiation and is among one of the lowest density planets known, which makes it a good candidate for future UV transit observations in the search for an extended hydrogen exosphere. © 2017. The American Astronomical Society. All rights reserved.
32 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/148-095-950-678-74X, pop00018 tex.type: [object Object]
Keywords: dept.phy; peer-reviewed; planetary systems; stars: individual (HAT-P-67); techniques: photometric; techniques: spectroscopic

Using Gaia as an astrometric tool for deep ground-based surveys - Casetti-Dinescu, Dana I.; Girard, Terrence M.; Schriefer, Michael (Proceedings of the International Astronomical Union, 2017)
Gaia DR1 positions are used to astrometrically calibrate three epochs’ worth of Subaru SuprimeCam images in the fields of globular cluster NGC 2419 and the Sextans dwarf spheroidal galaxy. Distortion-correction “maps” are constructed from a combination of offset dithers and reference to Gaia DR1. These are used to derive absolute proper motions in the field of NGC 2419. Notably, we identify the photometrically-detected Monoceros structure in the foreground of NGC 2419 as a kinematically-cold population of stars, distinct from Galactic-field stars. This project demonstrates the feasibility of combining Gaia with deep, ground-based surveys, thus extending high-quality astrometry to magnitudes beyond the limits of Gaia.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/110-283-973-036-247
Keywords: Galaxy: kinematics and dynamics; astrometry; dept.phy; galaxies: dwarf

Four sub-Saturns with dissimilar densities: Windows into planetary cores and envelopes - Petigura, Erik A.; Sinukoff, Evan; Lopez, Eric D.; Crossfield, Ian J. M.; Howard, Andrew W.; Brewer, John M.; Fulton, Benjamin J.; Isaacson, Howard T.; Ciardi, David R.; Howell, Steve B.; Everett, Mark E.; Horch, Elliott P.; et al. (The Astronomical Journal, 2017)
We present results from a Keck/HIRES radial velocity campaign to study four sub-Saturn-sized planets, K2-27b, K2-32b, K2-39b, and K2-108b, with the goal of understanding their masses, orbits, and heavy-element enrichment. The planets have similar sizes (RP=4.5-5.5 ), but have dissimilar masses (MP=16-60 ), implying a diversity in their core and envelope masses. K2-32b is the least massive (MP = 16.5 ± 2.7 M) and orbits in close proximity to two sub-Neptunes near a 3:2:1 period commensurability. K2-27b and K2-39b are significantly more massive at MP = 30.9 ± 4.6 M and MP = 39.8 ± 4.4 M, respectively, and show no signs of additional planets. K2-108b is the most massive at MP = 59.4 ± 4.4 M, implying a large reservoir of heavy elements of about ≈50 . Sub-Saturns as a population have a large diversity in planet mass at a given size. They exhibit remarkably little correlation between mass and size; sub-Saturns range from ≈6-60 M, regardless of size. We find a strong correlation between planet mass and host star metallicity, suggesting that metal-rich disks form more massive planet cores. The most massive sub-Saturns tend to lack detected companions and have moderately eccentric orbits, perhaps as a result of a previous epoch of dynamical instability. Finally, we observe only a weak correlation between the planet envelope fraction and present-day equilibrium temperature, suggesting that photo-evaporation does not play a dominant role in determining the amount of gas sub-Saturns accrete from their protoplanetary disks. © 2017. The American Astronomical Society. All rights reserved..
62 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/117-273-244-483-27X, pop00045 tex.type: [object Object]
Keywords: dept.phy; peer-reviewed; planets and satellites: composition; planets and satellites: detection; planets and satellites: dynamical evolution and stability; planets and satellites: formation; planets and satellites: gaseous planets; planets and satellites: interiors

Assessing the effect of stellar companions from high-resolution imaging of Kepler objects of interest - Hirsch, Lea A.; Ciardi, David R.; Howard, Andrew W.; Everett, Mark E.; Furlan, Elise; Saylors, Mindy; Horch, Elliott P.; Howell, Steve B.; Teske, Johanna; Marcy, Geoffrey W. (The Astronomical Journal, 2017)
We report on 176 close (<2″) stellar companions detected with high-resolution imaging near 170 hosts of Kepler Objects of Interest (KOIs). These Kepler targets were prioritized for imaging follow-up based on the presence of small planets, so most of the KOIs in these systems (176 out of 204) have nominal radii <6 . Each KOI in our sample was observed in at least two filters with adaptive optics, speckle imaging, lucky imaging, or the Hubble Space Telescope. Multi-filter photometry provides color information on the companions, allowing us to constrain their stellar properties and assess the probability that the companions are physically bound. We find that 60%-80% of companions within 1″ are bound, and the bound fraction is >90% for companions within 0.″5; the bound fraction decreases with increasing angular separation. This picture is consistent with simulations of the binary and background stellar populations in the Kepler field. We also reassess the planet radii in these systems, converting the observed differential magnitudes to a contamination in the Kepler bandpass and calculating the planet radius correction factor, X R = R p(true)/R p(single). Under the assumption that planets in bound binaries are equally likely to orbit the primary or secondary, we find a mean radius correction factor for planets in stellar multiples of X R = 1.65. If stellar multiplicity in the Kepler field is similar to the solar neighborhood, then nearly half of all Kepler planets may have radii underestimated by an average of 65%, unless vetted using high-resolution imaging or spectroscopy. © 2017. The American Astronomical Society. All rights reserved.
49 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/119-135-164-854-429, pop00043 tex.type: [object Object]
Keywords: binaries: visual; dept.phy; peer-reviewed; planets and satellites: detection; planets and satellites: fundamental parameters; techniques: high angular resolution; techniques: photometric

Resonance raman of BCC and normal skin - Liu, Cheng-hui; Sriramoju, Vidyasagar; Boydston-White, Susie; Wu, Binlin; Zhang, Chunyuan; Pei, Zhe; Sordillo, Laura; M.d, Hugh Beckman; Alfano, Robert R. (Optical Biopsy XV: Toward Real-Time Spectroscopic Imaging and Diagnosis, 2017)
The Resonance Raman (RR) spectra of basal cell carcinoma (BCC) and normal human skin tissues were analyzed using 532nm laser excitation. RR spectral differences in vibrational fingerprints revealed skin normal and cancerous states tissues. The standard diagnosis criterion for BCC tissues are created by native RR biomarkers and its changes at peak intensity. The diagnostic algorithms for the classification of BCC and normal were generated based on SVM classifier and PCA statistical method. These statistical methods were used to analyze the RR spectral data collected from skin tissues, yielding a diagnostic sensitivity of 98.7% and specificity of 79% compared with pathological reports.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/015-837-955-575-755, pop00046 tex.type: [object Object]
Keywords: Basal cell carcinoma; Basel cell carcinoma (BCC); Biopsy; Cell carcinoma; Diagnostic algorithms; Histology; Human skin; Human skin tissues; Laser excitation; Principal component analysis; Principal component analysis (PCA); Resonance; Resonance Raman spectra; Resonance Raman spectroscopy; Skin cancer; Skin cancers; Spectral differences; Statistical methods; Support vector machine (SVM); Support vector machines; Tissue; Tissue engineering; dept.phy

Rapid measurement of meat spoilage using fluorescence spectroscopy - Wu, Binlin; Dahlberg, Kevin; Gao, Xin; Smith, Jason; Bailin, Jacob (Imaging, Manipulation, and Analysis of Biomolecules, Cells, and Tissues XV, 2017)
Food spoilage is mainly caused by microorganisms, such as bacteria. In this study, we measure the autofluorescence in meat samples longitudinally over a week in an attempt to develop a method to rapidly detect meat spoilage using fluorescence spectroscopy. Meat food is a biological tissue, which contains intrinsic fluorophores, such as tryptophan, collagen, nicotinamide adenine dinucleotide (NADH) and flavin adenine dinucleotide (FAD) etc. As meat spoils, it undergoes various morphological and chemical changes. The concentrations of the native fluorophores present in a sample may change. In particular, the changes in NADH and FAD are associated with microbial metabolism, which is the most important process of the bacteria in food spoilage. Such changes may be revealed by fluorescence spectroscopy and used to indicate the status of meat spoilage. Therefore, such native fluorophores may be unique, reliable and nonsubjective indicators for detection of spoiled meat. The results of the study show that the relative concentrations of all above fluorophores change as the meat samples kept in room temperature (~19° C) spoil. The changes become more rapidly after about two days. For the meat samples kept in a freezer (~-12° C), the changes are much less or even unnoticeable over a-week-long storage.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/026-929-135-501-547, pop00136 tex.type: [object Object]
Keywords: Amino acids; Bacteria; Biological tissues; Biomolecules; Collagen; Flavin adenine dinucleotide; Fluorescence; Fluorescence spectroscopy; Fluorophores; Food microbiology; Histology; Meat food; Meats; Metabolism; Microbial metabolism; Molecular biology; NADH; Nicotinamide adenine dinucleotides; Nucleotides; Physiology; Rapid measurement; Relative concentration; Spectrum analysis; Spoilage; Tissue; Tryptophan; dept.phy

Optical biopsy using fluorescence spectroscopy for prostate cancer diagnosis - Wu, Binlin; Gao, Xin; Smith, Jason; Bailin, Jacob (Therapeutics and Diagnostics in Urology: Lasers, Robotics, Minimally Invasive, and Advanced Biomedical Devices, 2017)
Native fluorescence spectra are acquired from fresh normal and cancerous human prostate tissues. The fluorescence data are analyzed using a multivariate analysis algorithm such as non-negative matrix factorization. The nonnegative spectral components are retrieved and attributed to the native fluorophores such as collagen, reduced nicotinamide adenine dinucleotide (NADH), and flavin adenine dinucleotide (FAD) in tissue. The retrieved weights of the components, e.g. NADH and FAD are used to estimate the relative concentrations of the native fluorophores and the redox ratio. A machine learning algorithm such as support vector machine (SVM) is used for classification to distinguish normal and cancerous tissue samples based on either the relative concentrations of NADH and FAD or the redox ratio alone. The classification performance is shown based on statistical measures such as sensitivity, specificity, and accuracy, along with the area under receiver operating characteristic (ROC) curve. A cross validation method such as leave-one-out is used to evaluate the predictive performance of the SVM classifier to avoid bias due to overfitting.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/116-092-737-895-249, pop00138 tex.type: [object Object]
Keywords: Artificial intelligence; Biopsy; Cross validation; Diseases; Factorization; Fluorescence; Fluorescence spectroscopy; Fluorophores; Learning algorithms; Learning systems; Matrix algebra; Multivariant analysis; Nonnegative matrix factorization; Nucleotides; Optical biopsies; Prostate cancers; Redox ratio; Robotics; Support vector machines; Tissue; Urology; cross validation; dept.phy; fluorescence spectroscopy; machine learning; nonnegative matrix factorization; optical biopsy; prostate cancer; redox ratio; support vector machine

Chemical composition of young stars in the leading arm of the Magellanic system - Zhang, Lan; Moni Bidin, Christian; Casetti-Dinescu, Dana I.; Méndez, Réne A.; Girard, Terrence M.; Korchagin, Vladimir I.; Vieira, Katherine; van Altena, William F.; Zhao, Gang (The Astrophysical Journal, 2017)
Chemical abundances of eight O- and B-type stars are determined from high-resolution spectra obtained with the MIKE instrument on the Magellan 6.5 m Clay telescope. The sample is selected from 42 candidates for membership in the Leading Arm (LA) of the Magellanic System. Stellar parameters are measured by two independent grids of model atmospheres and analysis procedures, confirming the consistency of the stellar parameter results. Abundances of seven elements (He, C, N, O, Mg, Si, and S) are determined for the stars, as are their radial velocities and estimates of distances and ages. Among the seven B-type stars analyzed, the five that have radial velocities compatible with membership of the LA have an average [Mg/H] of -0.42 ±0.16, significantly lower than the average of the remaining two, [Mg/H] = -0.07 ±0.06, which are kinematical members of the Galactic disk. Among the five LA members, four have individual [Mg/H] abundance compatible with that in the LMC. Within errors, we cannot exclude the possibility that one of these stars has an [Mg/H] consistent with the more metal-poor, SMC-like material. The remaining fifth star has an [Mg/H] close to Milky Way values. Distances to the LA members indicate that they are at the edge of the Galactic disk, while ages are of the order of ∼50-70 Myr, lower than the dynamical age of the LA, suggesting a single star-forming episode in the LA. V LSR of the LA members decreases with decreasing Magellanic longitude, confirming the results of previous LA gas studies. © 2017. The American Astronomical Society. All rights reserved..
8 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/103-917-768-897-580, pop00058 tex.type: [object Object]
Keywords: dept.phy

The Kepler follow-up observation program. I. a catalog of companions to Kepler stars from high-resolution imaging - Furlan, E.; Ciardi, D. R.; Everett, M. E.; Saylors, M.; Teske, J. K.; Horch, E. P.; Howell, S. B.; van Belle, G. T.; Hirsch, L. A.; Gautier, T. N.; Adams, E. R.; Barrado, D.; et al. (The Astronomical Journal, 2017)
We present results from high-resolution, optical to near-IR imaging of host stars of Kepler Objects of Interest (KOIs), identified in the original Kepler field. Part of the data were obtained under the Kepler imaging follow-up observation program over six years (2009-2015). Almost 90% of stars that are hosts to planet candidates or confirmed planets were observed. We combine measurements of companions to KOI host stars from different bands to create a comprehensive catalog of projected separations, position angles, and magnitude differences for all detected companion stars (some of which may not be bound). Our compilation includes 2297 companions around 1903 primary stars. From high-resolution imaging, we find that ∼10% (∼30%) of the observed stars have at least one companion detected within 1″ (4″). The true fraction of systems with close (≲4″) companions is larger than the observed one due to the limited sensitivities of the imaging data. We derive correction factors for planet radii caused by the dilution of the transit depth: assuming that planets orbit the primary stars or the brightest companion stars, the average correction factors are 1.06 and 3.09, respectively. The true effect of transit dilution lies in between these two cases and varies with each system. Applying these factors to planet radii decreases the number of KOI planets with radii smaller than 2 R⊕ by ∼2%-23% and thus affects planet occurrence rates. This effect will also be important for the yield of small planets from future transit missions such as TESS. © 2017. The American Astronomical Society. All rights reserved.
161 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/078-308-144-589-565, pop00008 tex.type: [object Object]
Keywords: binaries: general; catalogs; dept.phy; peer-reviewed; planets and satellites: detection; surveys; techniques: high angular resolution; techniques: photometric

Combinatorial screening of Pd-based quaternary electrocatalysts for oxygen reduction reaction in alkaline media - Li, Jinyang; Stein, Helge S.; Sliozberg, Kirill; Liu, Jingbei; Liu, Yanhui; Sertic, Genevieve; Scanley, Ellen; Ludwig, Alfred; Schroers, Jan; Schuhmann, Wolfgang; Taylor, André D. (Journal of Materials Chemistry, 2017)
The implementation of electrochemical systems such as fuel cells has been hindered by the slow development of low cost high activity catalysts. Here we examine the oxygen reduction reaction performance of a combinatorial Pd-Au-Ag-Ti thin film library using high-throughput screening and correlate the electrochemical behavior to the crystallographic properties. We find compositions of ca. 40-60 at% Pd and 30-35 at% Au exhibit both a low overpotential of close to the value of pure Pt as well as high current density. We also observe a volcano-like relationship between the overpotential and the solid formation strain. This study provides compositional guidance towards the future synthesis of nanostructured quaternary Pd-Au-Ag-Ti alloys and suggests the potential for broader application of high-throughput electrochemical characterization by means of an automatic scanning droplet cell. © The Royal Society of Chemistry.
30 citations (Crossref) [2023-10-31] Citation Key Alias: pop00049 tex.type: [object Object]
Keywords: Catalyst activity; Combinatorial screenings; Crystallographic properties; Electrocatalysts; Electrochemical behaviors; Electrochemical characterizations; Electrochemical systems; Electrolytic reduction; Fuel cells; Gold; High current densities; High throughput screening; Oxygen reduction reaction; Reduction; Silver; Silver alloys; Throughput; Titanium alloys; dept.phy

Noble metal high entropy alloys - Sohn, Sungwoo; Liu, Yanhui; Liu, Jingbei; Gong, Pan; Prades-Rodel, Silke; Blatter, Andreas; Scanley, B. Ellen; Broadbridge, Christine C.; Schroers, Jan (Scripta Materialia, 2017)
A series of noble metal high entropy alloys with up to six constituent elements has been produced by casting. PtPdRhIrCuNi forms single-phase face-centered cubic solid solution, and its stability is confirmed by annealing experiments. This alloy deforms homogeneously to ~30% to a high ultimate compression strength of 1839MPa. We discuss rules for the formation of single-phase solid solution.
70 citations (Crossref) [2023-10-31]
Keywords: Annealing experiments; Compressive properties; Compressive property; Constituent elements; Entropy; FCC structure; Face-centered cubic; Fcc structures; High entropy alloys; Phase stability; Precious metals; Single phase; Solid solution; Solid solutions; Ultimate compression; dept.phy

Introducing an analytical solution and an improved one-factor gaussian copula model for the pricing of heterogeneous CDOs - Gao, Xin; Wu, Binlin; Schäfer, Tobias (International Journal of Financial Engineering, 2017)
This paper introduced an analytical solution and improved one-factor Gaussian copula models to the pricing of tranches of a Collateralized debt obligations (CDO) portfolio. Prices of CDO tranches are calculated and compared using the analytical model and different one-factor Gaussian copula models including a two-category heterogeneous model and a completely heterogeneous model that uses individual rate parameter and correlation coefficient for each reference entity in a CDO portfolio. When correlation among reference entities is low, the price calculated from the analytical model matches very well with the one-factor Gaussian copula models. However, as the correlation among reference entities increases, prices calculated using both the analytical solution and the homogeneous or two-category one-factor Gaussian copula models significantly deviate from the completely heterogeneous one-factor Gaussian copula model. This result verifies our belief that uniform parameters cannot completely capture all the heterogeneities in a CDO portfolio. Completely heterogeneous one-factor Gaussian copula model using individual rate parameters and correlation coefficients for each reference entities provides more reliable and accurate prices for structured securities.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/183-625-470-365-466, pop00170
Keywords: dept.phy

Carbon nanotube synthesis from block copolymer deposited catalyst - Woods, K; Silliman, J; Schwendemann, Todd C (International Journal of High Speed Electronics and Systems, 2017)
A block copolymer/metal-salt solution was used to deposit metal nanoparticles on substrates, from which carbon nanotubes (CNTs) were grown in a chemical vapor deposition (CVD) chamber. Mono and hybrid catalysts of Fe, Ni, and Co-nitrates were tested, and separately Co, Ni, and Cu-chlorides. In both cases cobalt/cobalt-hybrids produced the highest density of multi-wall carbon nanotubes (MWCNTs). Slight vertical growth, though sparse, was observed after growth at 800°C from a nickel catalyst on single-crystal aluminium oxide (~130nm diameter). © 2017 World Scientific Publishing Company.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/153-067-574-456-766 tex.type: [object Object]
Keywords: Aluminium oxide; Block copolymers; Carbon nanotube synthesis; Carbon nanotubes; Catalysts; Chemical vapor deposition; Chemical vapor depositions (CVD); Hybrid catalysts; Metal nanoparticles; Multiwalled carbon nanotubes (MWCN); Nanotubes; Nickel; Nickel catalyst; Vertical growth; Yarn; block copolymer; carbon nanotube; dept.phy; peer-reviewed

Quantitative characterization for identification of brain cancer surgical margin using resonance Raman spectroscopy - Zhou, Yan; Liu, Chenghui; Wu, Binlin; Yu, Xinguang; Cheng, Gangge; Zhang, Chunyuan; Alfano, R R (Frontiers in Optics, 2017)
A new criterion was developed to characterize brain tissue using resonance Raman spectroscopy, by which, negative margins of cancer can be differentiated from normal tissues. This method may help a surgeon better decide surgical margins. © OSA 2017.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/043-005-059-782-813 tex.type: [object Object]
Keywords: Brain cancer; Brain tissue; Diseases; Normal tissue; Quantitative characterization; Raman spectroscopy; Resonance Raman spectroscopy; Surgery; Tissue; dept.phy

Teaching Materials Science and Engineering (MSE) in the pre-college classroom as a vehicle for NGSS implementation - Granucci, Nicole; Jenkins, Carol; Bauer, Melanie; Gard, Ashley L.; Pinkerton, Bryn; Broadbridge, Christine (MRS Advances, 2017)
Adoption of Materials Science and Engineering (MSE) into the pre-college classroom is an ideal strategy for addressing Next Generation Science Standards (NGSS), specifically the Science and Engineering Practices. MSE offers core science and engineering topics that can be incorporated into existing Science, Technology, Engineering, and Mathematic (STEM) curricula through teaching modules. Using MSE as a teaching vehicle, the Center for Research on Interface Structures and Phenomena (CRISP) conducted a series of small-scale studies of its teacher professional development workshops and a student summer program, along with related teaching modules, in an effort to measure the contribution MSE has on students and K-12 STEM educators. Based on participant survey feedback, CRISP found improvement in students' MSE knowledge, interests, and career goals. For teachers, in addition to improving their MSE knowledge, they also increased their comfort and confidence in teaching MSE concepts in their classroom. These results provide evidence for the use of MSE modules as productive teaching tools for NGSS Science and Engineering Practices, as well as producing workforce-competitive STEM students. Copyright © Materials Research Society 2017.
1 citations (Crossref) [2023-10-31]
Keywords: Aerogels; Curricula; Education; Government interactions; Interface structures; Materials science and engineering; STEM (science; technology; engineering and mathematics); Science; technology; engineering; and mathematics; Science and engineering; Science standards; Standards; Students; Surveys; Teacher professional development; Teaching; Teaching materials; aerogel; dept.phy; education; government interactions; peer-reviewed

A component‐by‐component characterisation of high‐risk atherosclerotic plaques by multiphoton microscopic imaging - Jain, Manu; Wu, Binlin; Pisapia, David J; Salvatore, Steven P; Mukherjee, Sushmita; Narula, Navneet; Mukherjee, Sushmita; Narula, Navneet (Journal of Microscopy, 2017)
Aims: Atherosclerotic plaques vulnerable to rupture are almost always inflamed, and carry a large lipid core covered by a thin fibrous cap. The other components may include neovascularisation, intraplaque haemorrhage and spotty calcification. In contrast, stable plaques are characterised by a predominance of smooth muscle cells and collagen, and lipid core is usually deep seated or absent. This study is a proof of principle experiment to evaluate the feasibility of multiphoton microscopy (MPM) to identify aforementioned plaque components. Methods and Results: MPM is a nonlinear optical technique that allows imaging based on intrinsic tissue signals including autofluorescence and higher-order scattering. In our study, MPM imaging was performed on morphologically diverse aortic and coronary artery plaques obtained during autopsy. Various histologically verified plaque components including macrophages, cholesterol crystals, haemorrhage, collagen and calcification were recognised by MPM. Conclusions: Recognition of the distinct signatures of various plaque components suggests that MPM has the potential to offer next-generation characterisation of atherosclerotic plaques. The higher lateral resolution (comparable to histology) images generated by MPM for identifying plaque components might complement larger field of view and greater imaging depth currently available with optical coherence tomography imaging. As the next step MPM would need to be evaluated for intact vessel imaging ex vivo and in vivo. © 2017 The Authors Journal of Microscopy © 2017 Royal Microscopical Society
3 citations (Crossref) [2023-10-31] Citation Key Alias: jainComponentbycomponentCharacterisationHighrisk2017, lens.org/088-949-097-388-885 tex.type: [object Object]
Keywords: Aorta; Article; Atherosclerotic plaque; Calcinosis; Cholesterol; Collagen; Coronary Vessels; Hemorrhage; Humans; Image Processing; Computer-Assisted; Macrophages; Nonlinear Optical Microscopy; Plaque; Atherosclerotic; aorta; atherosclerotic plaque; autofluorescence; autopsy; bleeding; calcinosis; cholesterol; clinical article; collagen; coronary artery; coronary artery calcification; coronary blood vessel; dept.phy; ex vivo; ex vivo study; feasibility study; histopathology; human; human tissue; image processing; immunology; macrophage; macrophages; multiphoton microscopy; nonlinear optical microscopy; pathology; priority journal; procedures